A single-institution experience with 177Lu RPT workflow improvements and qualifying the SPECT/CT imaging for dosimetry - George, Siju C.; Tolakanahalli, Ranjini; Aguirre, Santiago; Kim, Taehyung Peter; Samuel, E. James Jebaseelan; Mishra, Vivek (Frontiers in Oncology, 2024)
Background and Purpose: Implementing any Radiopharmaceutical therapy (RPT) program requires a comprehensive review of system readiness, appropriate workflows, and training to ensure safe and efficient treatment delivery. A quantitative assessment of the dose delivered to targets and organs at risk (OAR) using RPT is possible by correlating the absorbed doses with the delivered radioactivity. Integrating dosimetry into an established RPT program demands a thorough analysis of the necessary components and system fine-tuning. This study aims to report an optimized workflow for molecular radiation therapy using 177 Lu, primarily focusing on integrating patient-specific dosimetry into an established Radiopharmaceutical program in a radiation oncology setting. We comprehensively reviewed using the Plan-Do-Check-Act (PDCA) cycle, including efficacy and accuracy of delivery and all aspects of radiation safety of the RPT program. The GE Discovery SPECT/CT 670DR™ system was calibrated per MIM protocol for dose calculation on MIM SurePlan TM MRT software. Jaszcak Phantom with 15-20 mCi of 177 Lu DOTATATE with 2.5 µM EDTA solution was used, with the Main Energy window defined as 208 keV +/-10% (187.6 -229.2 keV); the upper scatter energy window was set to 240 keV +/-5% (228 to 252 keV), while the lower scatter energy window was 177.8keV +/-5% (168.9 to 186.7keV). Volumetric Quality control tests and adjustments were performed to ensure the correct alignment of the table, NM, and CT gantry on SPECT CT. A comprehensive end-to-end (E2E) test was performed to ensure workflow, functionality, and quantitative dose accuracy.1Results: Workflow improvements and checklists are presented after systematically analyzing over 400 administrations of 177 Lu-based RPT. Injected activity to each sphere in the NEMA Phantom scan was quantified, and the MIM Sureplan MRT reconstruction images calculated activities within +/-12 % of the injected activity. Image alignment tests on the SPECT/CT showed a discrepancy of more than the maximum tolerance of 2.2 mm on any individual axis. As a result of servicing the machine and updating the VQC and COR corrections, the hybrid imaging system was adjusted to achieve an accuracy of < 1 mm in all directions.